New Design Thinking Tools for the Next Generation of Designer-Entrepreneurs. (28th July 2017) - Colombo, Sara; Cautela, Cabirio; Rampino, Lucia
Abstract: This paper analyses a new phenomenon to date poorly researched both in entrepreneurship and Design Thinking literature: Design-Intensive Start-ups (DIS), i.e. start-ups that focus on design as primary source for their development. Two main questions underpin the study: what are the specific features that describe design-intensive start-ups? Which are possible conceptual tools supporting designers in the creation of their own design-based enterprises? A multiple case studies protocol was adopted to investigate the first question. According to our results, DIS diverge from New-Technology Start-ups on several dimensions, and represent an alternative entrepreneurial model, which is not supported by extant literature. Currently, there are no tools helping designers to become entrepreneurs. Therefore, we developed a set of Design Thinking tools addressing the specific traits of DIS in the steps of their creation and evolution. Such tools are intended to support the decision-making process of designers-entrepreneurs in the foundation of their own start-ups.